2007
DOI: 10.1007/s10549-007-9789-z
|View full text |Cite
|
Sign up to set email alerts
|

Additive effects of a prolactin receptor antagonist, G129R, and herceptin on inhibition of HER2-overexpressing breast cancer cells

Abstract: Breast cancers overexpressing human epidermal growth factor receptor 2 (HER2) have been reported to have higher proliferative and metastatic activity in the presence of autocrine prolactin (PRL), indicating potential cooperation between HER2 and the PRL receptor (PRLR) during breast cancer progression. PRL can induce the tyrosine phosphorylation of HER2 which stimulates mitogen-activated protein kinase (MAPK) activity. To determine if this transactivation of HER2 by PRL contributes to anti-HER2 therapy resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…Carcinogen-treated and syngeneic murine models of mammary carcinoma , Beck et al 2003, Tomblyn et al 2005, xenografts of established breast cancer cell lines in athymic nude mice , and clonogenic survival assays of breast cancer cell lines and clinical tumors (Howell et al 2008) predict that hPRL-G129R will have clinical utility. In vitro studies also suggest that hPRL-G129R will enhance the effectiveness of conventional breast cancer chemotherapies (Chen et al 1999, Howell et al 2008, Scotti et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinogen-treated and syngeneic murine models of mammary carcinoma , Beck et al 2003, Tomblyn et al 2005, xenografts of established breast cancer cell lines in athymic nude mice , and clonogenic survival assays of breast cancer cell lines and clinical tumors (Howell et al 2008) predict that hPRL-G129R will have clinical utility. In vitro studies also suggest that hPRL-G129R will enhance the effectiveness of conventional breast cancer chemotherapies (Chen et al 1999, Howell et al 2008, Scotti et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…The use of dasatinib, a small molecule inhibitor of src has proven beneficial to HER2-positive breast cancer when used in combination with trastuzumab (33). Furthermore, use of trastuzumab in combination with the PRLR antagonist, G129R, has also been shown to have an additive inhibitory effect on HER2 and MAPK phosphorylation, and the proliferation of T-47D and BT-474 breast cancer cells both in vitro and in vivo (4). Finally, attacking multiple hallmarks of cancer simultaneously using various cancer therapeutics is under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that PRL is expressed in the epithelium of human breast cancers and that PRL receptor (PRLR) levels are higher in a majority of benign and malignant mammary tumors than the surrounding normal tissue (1,2). In addition, PRL and PRLR appear to have a role in both hormone responsive and hormone-independent breast cancers (3)(4)(5). For example, PRL has been shown to interact synergistically with estrogen and progesterone to promote cancerous growth; the receptors for these ligands are often co-expressed in primary breast cancers (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of the prolactin receptor using G129R (prolactin receptor antagonist) inhibits ErbB2 phosphorylation, suggesting an opportunity for combination therapy. Consistent with this possibility, combination of Herceptin (anti-HER2 therapeutic antibody) and G129R has an additive effect in inhibiting both MAPK activation and growth of BT474 breast cancer cells in cell culture and in xenograft mouse models (Scotti et al 2008). Further studies are needed to explore this novel therapeutic strategy for patients with HER-positive breast cancers that also express autocrine prolactin.…”
Section: Human Breast Cancermentioning
confidence: 92%